Information for patients: should we reconsider our assumptions? - van der Waarde, Karel (InfoDesign, 2023)
In order to take medicines correctly, it is essential that people receive suitable information. Without information it is difficult to consider, take, store, and discard medicines. At the moment, many people have difficulties to find, read, understand, and apply information about medicines. In the European Union, most information about medicines is presented in a text format. Very few visuals are used. Furthermore, information about medicines does not make much use of the digital opportunities. The logical next steps are to improve the design of visual information about medicines, and to embrace digital opportunities. However, the regulatory frameworks that govern information about medicines need to be modified. The regulations need to focus on usability, understanding, findability, and relevance. Experiments and prototypes are essential to find out what kinds of information and formats are effective. This requires a shift towards a ‘digital design strategy based on healthcare outcomes.’